The problem of hanging out with the crowd - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case centers on examples of crowd crush. It refers to accidents taking place during concerts, one in Ohio, USA, and another one in Denmark, with a particular focus on the crush at a Wal-Mart store during the Black Friday sales. How can businesses dealing with large crowds best protect their customers from these kinds of dangers?